A photosynthesis operon in the chloroplast genome drives speciation in evening primroses. Issue 8 (28th May 2021) - Zupok, Arkadiusz; Kozul, Danijela; Schöttler, Mark Aurel; Niehörster, Julia; Garbsch, Frauke; Liere, Karsten; Fischer, Axel; Zoschke, Reimo; Malinova, Irina; Bock, Ralph; Greiner, Stephan
Abstract: Genetic incompatibility between the cytoplasm and the nucleus is thought to be a major factor in species formation, but mechanistic understanding of this process is poor. In evening primroses ( Oenothera spp.), a model plant for organelle genetics and population biology, hybrid offspring regularly display chloroplast–nuclear incompatibility. This usually manifests in bleached plants, more rarely in hybrid sterility or embryonic lethality. Hence, most of these incompatibilities affect photosynthetic capability, a trait that is under selection in changing environments. Here we show that light-dependent misregulation of the plastid psbB operon, which encodes core subunits of photosystem II and the cytochrome b 6 f complex, can lead to hybrid incompatibility, and this ultimately drives speciation. This misregulation causes an impaired light acclimation response in incompatible plants. Moreover, as a result of their different chloroplast genotypes, the parental lines differ in photosynthesis performance upon exposure to different light conditions. Significantly, the incompatible chloroplast genome is naturally found in xeric habitats with high light intensities, whereas the compatible one is limited to mesic habitats. Consequently, our data raise the possibility that the hybridization barrier evolved as a result of adaptation to specific climatic conditions. Abstract : Photosynthesis genes encoded on the chloroplast genome establish hybridization barriers.